THE DIFFICULTIES FACED BY THE STUDENTS IN ANSWERING THE WRITTEN EXPRESSION SECTION OF THE TOEFL TEST - Mainar Fitri (Indonesian Journal of Integrated English Language Teaching, 2017)
TOEFL test is one of the requirements for the students of English Study Program FKIP UNRI to finish their study at S1 Degree.  Based on the researcher’s observation, most of the students did not pass the TOEFL Test.  The students followed the test for several times till they reached the passing grade. It seemed that the students got difficulties in answering the TOEFL Test. So, in this research the researcher focused on analyzing the students’ difficulties in answering the Written Expression section of the TOEFL test.  The aims of this research were to identify the categories of items in the Written Expression section of the TOEFL test which were difficult for the third-year students of English Study Program FKIP-UNRI . and to identify which categories of items that were easy for the students. This research was a quantitative research. The researcher analyzed the categories of items tested in TOEFL test, especially in the Written Expression section. There were 12 categories of items tested in the Written Expression section of the TOEFL test based on Longman Preparation Course for the TOEFL Test by Deborah Phillips (2000: 144-221). The categories consisted of subject-verb agreement, parallel structure, comparative and superlative, the use of the verbs, the forms of the verbs, passive verbs, nouns, pronouns, adjectives and adverbs, articles, prepositions and usages   The result of the research showed that there were 10 categories of items that were difficult for the students. The categories were parallel structures, comparatives and superlatives, the use of the verbs, passive verbs, nouns, pronouns, adjectives and adverbs, articles, prepositions and usages.  While the categories of items which were considered easy for the students were subject-verb agreement and the forms of the verbs. So, in general, the students got difficulties in answering the Written Expression section of the TOEFL test.